مستوى الكفاءة اللغوية عند تلاميذ مرحلة التعليم الابتدائي - كرشو, لزهر; معامير, الأزهر (جامعة الوادي - university of Eloued, 2022)
يجمع كل الباحثين في الحقل التربوي في الجزائر أن مستوى الكفاءة اللغوية في اللغة العربية؛ مشافهة وكتابة، يعرف انحدارا مستمرا رغم الإصلاحات التي مست المناهج التربوية، والنظام التربوي عموما. فلا شك أن هناك أسبابا فطرية وأخرى مكتسبة، يعزى إليها هذا الوضع المزري الذي آل إليه الخطاب العربي الفصيح؛ على مستوى المعلمين والمتعلمين. ففي ورقة البحث هذه، سنعرض إلى بعض الأسباب الفطرية التي أشارت إليها بعض نظريات اكتساب اللغة، كما سنتطرق إلى أهم الأسباب المكتسبة التي أدت إلى إحداث هذه الإختلالات العميقة، سواء على مستوى بناء المناهج أو تكوين المدرسين أو المكونين، أوغيرها من العوامل الأخرى، وسنطرح في نهاية البحث بعض الاقتراحات التي من شأنها أن تسهم في إنعاش مستوى الأداء اللغوي العربي الفصيح لدى تلامذتنا وطلبتنا. الكلمات المفتاحية: الكفاءة اللغوية؛ المنهج التربوي؛ مرحلة التعليم الابتدائي؛ نظريات اكتساب اللغة؛ البيئة اللغوية. All researchers in the educational field in Algeria agree that the level of linguistic competence in the Arabic language; in oral and in writing, it knows a continuous decline despite the reforms in the educational curricula, and the educational system in general. There is no doubt that are innate and acquired causes to which this dismal situation has devolved into the eloquent Arab discourse. for teachers and learners. In this research paper, we will present some of the innate reasons referred to by some theories of language, and we will also address the most important acquired reasons that led to theseprofoundimbalances, whether on the level of curriculum building or teacher training or trainers. or other factors. At the end of The research we provide some suggestions that would contribute to reviving the level of eloquent Arabic language performance of our pupils and students . linguistic competence educational curriculum, Primary education stage. Language acquisition theories. :linguistic environment.
مقال
Keywords: الكفاءة اللغوية؛ المنهج التربوي؛ مرحلة التعليم الابتدائي؛ نظريات اكتساب اللغة؛ البيئة اللغوية.; linguistic competence educational curriculum, Primary education stage. Language acquisition theories. :linguistic environment.